The functional model of optimization of the special physical preparation of students in the period of flying practice - V.N. Kirpenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
It is considered approaches to optimization special physical preparation of students during the period of flying practice. For the construction of functional model of such system new information IDEF technology is utillized (ICAM Definition). The feature of technology is gradual introduction all large levels of working out in detail (decoupligs). It is marked that it is expedient to carry out a decouplig before functions which will realize leaders of physical preparation and instructor of flying preparation. It is well-proven that on the stage of research of function a fundamental place is occupied by a functional design. The result of optimization of maintenance of teaching is systematization of knowledge, abilities, facilities of development and support professionally of meaningful qualities of students. The hierarchical levels of process of systematization of maintenance of teaching are recommended. It is offered directions of realization of functional model through conditioning optimization of pedagogical activity of teacher.